The Effects of Secondary Pre-Tightening of the Clamping Cable Nodes on Yielding U-Shaped Steel Supports for Use in Deep Soft Rock Roadways - Yubing Huang; Hongdi Tian; Xuepeng Wang; Yucheng Wang; Huayu Yang (Applied Sciences)
Secondary pre-tightening of clamping cable joints can effectively improve the load-bearing performance of U-shaped steel supports. However, the underlying mechanism of secondary pre-tightening has remained a critical knowledge gap in ground control engineering, and its design still relies on empirical approaches without theoretical guidance. To address these challenges, this study proposes a novel mechanistic framework integrating mathematical modelling, experimental validation, and parametric analysis. Specifically, a first-principle-based mathematical expression for the slip resistance of clamping cable joints under secondary pre-tightening was derived, explicitly incorporating the effects of bolt torque and interfacial friction; and a dual-phase experimental protocol combining axial compression tests and numerical simulations was developed to systematically quantify the impacts of initial pre-tightening torque, secondary pre-tightening torque (T2), and the timing of secondary pre-tightening (u/umax). Three groundbreaking thresholds were identified, as follows: critical initial pre-tightening torque (T1 > 250 N·m) beyond which secondary pre-tightening becomes ineffective (<5% improvement); minimum effective secondary pre-tightening torque (T2/T1 > 1) for significant load-bearing enhancement; and the optimal activation window (u/umax < 50%) balancing capacity gain (<10%) and deformation control. These findings establish the first quantitative design criteria for secondary pre-tightening applications, transitioning from empirical practice to mechanics-driven optimization.